2022
DOI: 10.1186/s12877-022-03515-4
|View full text |Cite
|
Sign up to set email alerts
|

Pressure pain threshold and somatosensory abnormalities in different ages and functional conditions of post-stroke elderly

Abstract: Background Somatosensory deficits and abnormal pain sensitivity are highly prevalent among stroke survivors, which negatively impacts their quality of life and recovery process. However, the factors for pressure pain threshold (PPT) and somatosensory abnormalities in post-stroke elderly remain unknown. The aim of this study was to explore the effects of age, side and other functional conditions, such as spasticity and motor functions, on PPT and sensory abnormalities among elderly after stroke.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Some authors have observed, with clinical thermography and PTT, that acute inflammatory processes also increase pain sensitivity as the temperature increases [ 57 , 58 ], while in chronic pathologies, no correlation has been observed between the decrease in temperature and the decrease in pain sensitivity [ 59 ]. In patients with brain lesions, pain sensitivity is correlated to somatosensory abnormalities of the hypoalgesia type [ 60 ], in addition to thermal and sensory differences according to the level of spastic involvement. This author observed differences according to age, with older patients showing greater sensitivity to pain compared to younger patients, and the affected sides of elderly patients showing greater sensitivity than those of younger patients [ 60 ] In this regard, our results contrast with the data provided by these authors, since this clinical situation regarding thermal differences and PTT results was not observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have observed, with clinical thermography and PTT, that acute inflammatory processes also increase pain sensitivity as the temperature increases [ 57 , 58 ], while in chronic pathologies, no correlation has been observed between the decrease in temperature and the decrease in pain sensitivity [ 59 ]. In patients with brain lesions, pain sensitivity is correlated to somatosensory abnormalities of the hypoalgesia type [ 60 ], in addition to thermal and sensory differences according to the level of spastic involvement. This author observed differences according to age, with older patients showing greater sensitivity to pain compared to younger patients, and the affected sides of elderly patients showing greater sensitivity than those of younger patients [ 60 ] In this regard, our results contrast with the data provided by these authors, since this clinical situation regarding thermal differences and PTT results was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with brain lesions, pain sensitivity is correlated to somatosensory abnormalities of the hypoalgesia type [ 60 ], in addition to thermal and sensory differences according to the level of spastic involvement. This author observed differences according to age, with older patients showing greater sensitivity to pain compared to younger patients, and the affected sides of elderly patients showing greater sensitivity than those of younger patients [ 60 ] In this regard, our results contrast with the data provided by these authors, since this clinical situation regarding thermal differences and PTT results was not observed. This discrepancy in performance may be due to the degree of homogeneity of the lesion, which was much higher as all participants were hemiplegic patients, whereas in our study, we included several types of neurological sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Denny-Brown [9] pointed out that the disruption of the anterior primary motor cortexM1 region, primary and secondary parietal sensory areas is necessary to induce PSS. The primary sensory cortexS1 and secondary sensory areas (such as prefrontal cortex and parietal lobe) are activated by peripheral sensory stimulation, which sensory network reorganization is bene cial to the relief of spasticity [12] .The ber connection between the cerebral sensory cortex and the motor cortex is destroyed after stroke, while somato-sensory stimulation can promote the reconstruction of the connection ber, then promote the recovery of motor function [13] .…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of hemiplegia after a stroke is essential, and rehabilitation [6], as well as other interventions [7,8], offer interesting results on the motor skills of the affected muscle groups. However, the painful nature and the sensory alterations that accompany spastic hemiplegia continue to represent a therapeutic challenge that does not always reach goals [9], especially because the neuroplastic changes secondary to the pain syndrome complicate its treatment when they become chronic and are not treated promptly. Like all neuropathic pain, its treatment with anti-inflammatories is ineffective and prone to side effects.…”
Section: Introductionmentioning
confidence: 99%